Health behaviors of people over the age of 65 residing in the home environment - Bartoszek, Agnieszka; Nowicki, Grzegorz; Kocka, Katarzyna; Ślusarska, Barbara; Bartoszek, Adrian; Łuczyk, Marta; Deluga, Alina; Zielonka, Edyta (Journal of Education, Health and Sport, 2017)
Admission. Lifestyle elements favorably affect health in old age include proper diet and eating habits, the optimal level of physical activity, adequate sleep, satisfying social relationships, skillful use of free time and knowledge of health prevention. Aim of the study. Assessment of health-related behaviors in a group of people over the age of 65 living in the home environment in selected socio-demographic conditions. Material and methods. The study was conducted in February and March 2014. The material consisted of 110 people over 65 years of age. The research method was used in the job diagnostic survey. It was used as a research tool original questionnaire assessing the behavior of seniors in the area: diet, physical activity, sleep and rest, the use of stimulants and sources of stress and ways of coping with stress. Results. The study results, that the majority of respondents eat 4-5 meals a day (50.9%; n = 43). Daily activity declares 29.1% (n = 32) tested. The most popular form of physical activity among respondents over 65 years of age are walking (75.4%; n = 83). Smoke 28.2% (n = 32) tested. In most of the subjects they consume alcohol occasionally (83.6%, n = 92) or several times per week (16.4%, n = 18). Sources of stress in the population of seniors are primarily conflicts in the family (24.5%; n = 27), loneliness (21.8%; n = 24) and financial problems (20%; n = 22). Conclusions. Studies have shown that socio-demographic factors significantly influence health-related behaviors presented by seniors. Assessment of the level and quality of health behavior allows you to make educational activities, care and treatment for people in aging and old age.